Reasonable Parts of the Case For the Scholar Muhammad Baqir bin Hussain Khan Al-Balaki - Study, Investigation and Comment - Masoud Muhammad Ali, (Islamic Sciences Journal, 2025)
ABSTRACT The current study deals with a scientific investigation of the parts of the rational case between what is agreed upon and what is different in it, and show the necessity of submission in the case to the difference between doubt, hesitation and ratification, and the difference between the verbal ratio and the eternal predicate ratio, through the following: A statement of the applicants' opinion that the parts of the case are three, and they were silent about the percentage in between. The later speakers differed in directing the silence of the forerunners on opinions: Some of them said: Their silence is evidence that the applicants consider it neither a part nor a condition . Some said: their silence is not a sign of denial, rather they considered it a condition, not a part. Some others said the opposite, that is, consider it a part , not a condition. The author has an analysis of this dilemma, guidance for the statements of the two parties, and a discussion of their opinions in response, guidance, and then reconciliation including clarifying the meaning of ratification between the opinions of theologians and philosophers, then discussing their opinions collectively, then guidance, then weighting. Included also, a statement of the meaning of science between how, addition and emotion, then reconciling opinions and making the dispute verbal.